1997
DOI: 10.1002/(sici)1097-4644(19970915)66:4<532::aid-jcb12>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Induction of intracellular ceramide by interleukin-1β in oligodendrocytes

Abstract: The sphingomyelin pathway has been implicated in mediating the effect of several extracellular agents leading to important biochemical and cellular changes. The aim of this investigation is to study interleukin-1 beta (IL-1 beta) signaling in oligodendrocytes. For this purpose, the CG4 oligodendrocyte cells were differentiated and incubated with IL-1 beta. This treatment induced a time- and dose-dependent increase of the endocellular ceramide. To mimic the effect of the elevation of endogenous ceramide, the CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 40 publications
(41 reference statements)
0
37
0
1
Order By: Relevance
“…1). However, a high level of expression of IL-1RI has been reported in this cell type (Brogi et al 1997;Blasi et al 1999). Consequently, the low level of expression of IL-1RI in our microglial cell cultures may reflect expression of IL-1RI on O 2 A progenitor cells, but not on microglial cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…1). However, a high level of expression of IL-1RI has been reported in this cell type (Brogi et al 1997;Blasi et al 1999). Consequently, the low level of expression of IL-1RI in our microglial cell cultures may reflect expression of IL-1RI on O 2 A progenitor cells, but not on microglial cells.…”
Section: Discussionmentioning
confidence: 89%
“…Expression of IL-1RI, IL-1RII and IL-1RAcP has also been reported on astrocytes (Tomozawa et al 1995;Zetterstrom et al 1998;Pousset et al 2001) and oligodendrocytes (Brogi et al 1997;Blasi et al 1999).…”
mentioning
confidence: 89%
“…8 In other studies, the generation of ceramide by interleukin-1b in dendrocytes was not associated with apoptosis, although exogenously added ceramide killed dendrocytes. 51 Furthermore, ceramide was not found to be an upstream messenger in the cell death signaling mediated by Fas. In these studies, ceramide generation was regarded as a consequence rather than a cause of apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the ultrastructural characteristics that we have described in the present model resemble the ones observed in a model of demyelination using Theiler's virus. 40 IL-1 per se has been shown to be cytotoxic to adult oligodendrocytes in vitro, 14,15 while the treatment of rats subjected to experimental autoimmune encephalomyelitis (EAE) with IL-1ra, an endogenous antagonist of IL-1, resulted in delayed and milder disease. 41,42 Moreover, certain IL-1 polymorphisms and a high ratio of IL-1 over IL-1ra production have been associated with increased susceptibility to relapse-onset multiple sclerosis in families.…”
Section: Il-1 and Demyelinationmentioning
confidence: 99%
“…4,10,11 Moreover, blocking IL-1 action reduces neuronal loss and inflammation induced by experimental brain insults 9,12,13 and IL-1 has been shown to be cytotoxic for oligodendrocytes both in vitro and in vivo. 14,15 On the other hand, although most of the evidence points to a detrimental role of IL-1 in MS, it has been shown to promote repair of cuprizone-derived demyelination via IGF-1. 16 It has been shown that a single-bolus injection of IL-1 into the CNS parenchyma gives rise to delayed and localized neutrophil (PMN) recruitment, but no overt damage to CNS integrity.…”
mentioning
confidence: 99%